Circadian and sleep–wake rhythm alterations in isolated REM sleep behavior disorder: biomarkers of prodromal α-synucleinopathy - Carpi, Matteo; Liguori, Claudio (Frontiers in Neuroscience, 2025)
Growing evidence highlights a tight interplay linking circadian and sleep–wake disturbances to the pathophysiology of neurodegenerative disorders. In α-synucleinopathies, three key points have emerged: (1) circadian and sleep–wake disruptions may increase the risk of neurodegeneration; (2) these alterations reflect widespread dysfunction in neural circuits regulating sleep, wakefulness, and biological rhythms; and (3) the prodromal condition of isolated rapid eye movement (REM) sleep behavior disorder (iRBD) offers a unique window into early pathological changes, as it is characterized by neurodegeneration in brainstem structures critical for sleep–wake regulation and REM sleep control. Hence, sleep- and circadian-related biomarkers may represent feasible tools for early diagnosis, prevention, and treatment across the spectrum of α-synucleinopathies. However, despite their potential, diagnostic or therapeutic pathways grounded in sleep and circadian biology have yet to be systematically explored or validated, and key questions remain, including the trajectories that characterize the clinical progression from iRBD to overt α-synucleinopathies. Key challenges include translational barriers, inter-individual variability in biomarker profiles, and the need for longitudinal studies to define clinically actionable thresholds. Against this backdrop, this mini-review synthesizes current evidence on sleep–wake rhythm alterations in iRBD as a prodromal stage of α-synucleinopathy-driven neurodegeneration. Candidate circadian biomarkers are discussed, including objective parameters from long-term actigraphic monitoring, encompassing rest–activity rhythms modeled with parametric and non-parametric approaches, as well as physiological indicators such as dim light melatonin onset and core body temperature.